DIGLOSSIA IN RELIGIOUS ACTIVITIES IN PURI AGUNG TEGAL TAMU IN GIANYAR - Sang Ayu Isnu Maharani (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2012)
Language varieties may be classified according to the users of the language. Regarding the so-cial stratification of the society where the language is spoken, language can divided into high, middle and lower variety. Language varieties which concern with social stratification between upper and lower class speaker is mentioned as diglossia. This research aims at identifying types and meaning of diglossia occur in Puri Agung Tegal Tamu and also investigating what factors influenced the used of diglossia in religious activities since Puri becomes the center of culture and a place where the civiliza-tion begins. In Puri Agung Tegal Tamu of Gianyar Regency, religous activities often take place such as maaturan, nunas tirta and nunas muput or ngantebin. This research concludes that the diglossia is classified into formal diglossia. Its occurrence in religious activities such as: inggih (yes), uning (know), elingang (remember) as part of H language variety and nah (yes), tawang (know), inget (remember) as part of L language variety. Its meaning for H class speaker is to express the power, and it signified respect by the L class speaker. It is influenced by several factors such as: field, mode and tenor. Keywords: diglossia, religious activities, and Puri .